SISTEM OTOMATIS MONITORING DAN PENGENDALIAN KEKERUHAN AIR BERBASIS ARDUINO DENGAN METODE FUZZY - Niki Ratama; Munawaroh Munawaroh; Hadi Zakaria (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
Water turbidity is a major concern in maintaining water quality for daily use. Manual monitoring of turbidity levels is often inefficient and prone to errors. This study aims to design and implement an automatic system capable of monitoring and controlling water turbidity using Arduino and fuzzy logic methods. The system employs a turbidity sensor to detect the clarity level, which is then processed through fuzzy logic to determine the activation of a water pump. The testing results show that the system can respond to turbidity changes in real-time with up to 95% accuracy. Fuzzy logic provides more adaptive control compared to binary logic approaches. This system demonstrates high effectiveness in maintaining water quality automatically, especially in environments requiring stable water clarity levels.